Peningkatan Pemahaman Masyarakat Trimulyo Genuk Semarang Mengenai Aspek Hukum Perjanjian Pinjaman Online - Endang Setyowati; Muhammad Iftar Aryaputra; Ani Triwati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
One of the technological developments in the economic sector that has had a big influence is Fintech, which is an innovation in the field of technology in terms of transactions for giving and receiving loans, without having to meet face to face, or what is better known as online loans. The legal provisions governing conventional agreements are the same as the legal provisions governing online agreements. Due to the negative impact of illegal online loans, it is necessary for the Community Service Team (PkM) of the Faculty of Law, University of Semarang (USM) to hold outreach and counseling with the theme